Efficacy and safety of the direct oral anti‐coagulants in patients with cerebral vein thrombosis: A systematic review and meta‐analysis. (31st March 2022) - Riva, Nicoletta; Galea, Francesca; Buhagiar, Isaac; Gatt, Alex; Calleja‐Agius, Jean
Summary: Vitamin K antagonists (VKAs) are the standard oral anti‐coagulant treatment for patients with cerebral venous thrombosis (CVT). However, the direct oral anti‐coagulants (DOACs) started replacing VKAs also in this setting. We aimed to evaluate safety and efficacy of the DOACs for CVT treatment. We performed a systematic review and meta‐analysis (PROSPERO protocol registration number CRD42020191472). The electronic databases MEDLINE, EMBASE and CENTRAL were searched from inception to January 2022. We included randomised controlled trials (RCTs) and observational studies, enrolling at least 10 adult patients with CVT treated with any DOACs. Twenty‐three studies were included, for a total of 618 CVT patients treated with DOACs (treatment duration range 3–12 months). Mortality rate was 1.76% [95% confidence interval (CI) 0.70%–3.24%; I 2  = 0%; 5/428 patients, 18 studies]; major bleeding 2.41% (95% CI 1.26%–3.91%; I 2  = 1.5%; 12/534 patients, 21 studies); recurrent thrombosis 2.05% (95% CI 1.04%–3.37%; I 2  = 0%; 10/577 patients, 21 studies); excellent neurological outcome 85.9% (95% CI 79.0%–91.7%; I 2  = 63.7%; 289/340 patients, 13 studies); vessel recanalisation 89.0% (95% CI 82.9%–93.9%; I 2  = 62.7%; 316/359 patients, 16 studies). No significant differences emerged by study design (RCTs vs. observational studies) or by treatment (DOACs vs. VKAs). This systematic review showed that the DOACs might represent a reasonable oral anti‐coagulant treatment option for CVT patients.